2016
DOI: 10.1016/j.tins.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Defining Auditory-Visual Objects: Behavioral Tests and Physiological Mechanisms

Abstract: Crossmodal integration is a term applicable to many phenomena in which one sensory modality influences task performance or perception in another sensory modality. We distinguish the term binding as one that should be reserved specifically for the process that underpins perceptual object formation. To unambiguously differentiate binding form other types of integration, behavioral and neural studies must investigate perception of a feature orthogonal to the features that link the auditory and visual stimuli. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
96
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(104 citation statements)
references
References 84 publications
(128 reference statements)
8
96
0
Order By: Relevance
“…Recently, Stekelenburg et al (2013) and Roa Romero et al (2016b) also reported group differences in multisensory ERPs without showing effects in behavioral data. In an interesting framework on multisensory processing, Bizley et al (2016) suggested different stages of multisensory integration, in which the initial integrative processing can occur, at least partially, independent of later perception-related processing. In line with this proposal, the initial processing and integration could be disturbed in the SIFI trials in SCZ, whereas the later perceptual stages might be still intact.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Stekelenburg et al (2013) and Roa Romero et al (2016b) also reported group differences in multisensory ERPs without showing effects in behavioral data. In an interesting framework on multisensory processing, Bizley et al (2016) suggested different stages of multisensory integration, in which the initial integrative processing can occur, at least partially, independent of later perception-related processing. In line with this proposal, the initial processing and integration could be disturbed in the SIFI trials in SCZ, whereas the later perceptual stages might be still intact.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the use of realistic stimuli under well-controlled conditions can provide an insight on the mechanisms of multisensory combination as they often occur. It also provides for a preservation of stimulus identity from a common audiovisual source, which promotes multisensory binding [45]. From this point of view it is equally arguable that realistic and congruent stimuli could be associated to higher levels of perceived common causality and integration than if more abstract stimuli were used.…”
Section: Discussionmentioning
confidence: 99%
“…There is also substantial evidence for integration of cross-modal signals later in the decisionmaking process. Whether correlates of multisensory evidence accumulation and decision-making are observed in sensory cortex as well as, or instead of, in higher areas may depend on the nature of the task and on whether multisensory signals are perceived as originating from a single perceptual object [5].…”
Section: Towards a Synthesismentioning
confidence: 99%
“…Integrating signals across sensory modalities can therefore reduce the inherent uncertainty within any sensory estimate and so improve performance in perceptual decisionmaking tasks. In the mammalian brain, the neural processes underlying decision-making [3,4] and multisensory integration [5][6][7] have become increasingly well understood but remain largely independent lines of investigation. In particular, it remains an open question at what point(s) in the decision-making process information is combined across modalities.…”
Section: Introductionmentioning
confidence: 99%